Stable Isotope Clues to the Formation and Evolution of Refrozen Melt Ponds on Arctic Sea Ice. Issue 12 (7th December 2018) - Tian, L.; Gao, Y.; Ackley, S. F.; Stammerjohn, S.; Maksym, T.; Weissling, B.
Abstract: Sea ice is one of the determining parameters of the climate system. The presence of melt ponds on the surface of Arctic sea ice plays a critical role in the mass balance of sea ice. A total of nine cores was collected from multiyear ice refrozen melt ponds and adjacent hummocks during the 2015 Arctic Sea State research cruise. The depth profiles of water isotopes, salinity, and ice texture for these sea ice cores were examined to provide information about the development of refrozen melt ponds and water balance generation processes, which are otherwise difficult to acquire. The presence of meteoric water with low oxygen isotope values as relatively thin layers indicates melt pond water stability and little mixing during formation and refreezing. The hydrochemical characteristics of refrozen melt pond and seawater depth profiles indicate little snowmelt enters the upper ocean during melt pond refreezing. Due to the seasonal characters of deuterium excess for Arctic precipitation, water balance calculations utilizing two isotopic tracers (oxygen isotope and deuterium excess) suggest that besides the melt of snow cover, the precipitation input in the melt season may also play a role in the evolution of melt ponds. The dual‐isotope mixing model developed here may become more valuable in a future scenario of increasing Arctic precipitation. The layers of meteoric origin were found at different depths in the refrozen melt pond ice cores. Surface topography information collected at several core sites was examined for possible explanations of different structures of refrozen melt ponds. Plain Language Summary: The connection between precipitation and the retreat and expansion of sea ice is poorly understood. This paper brings a new approach to investigate meteoric origins of sea ice in the polar regions. We propose to investigate moisture sources for precipitations and the accumulation of snow based on isotopic analysis of sea ice samples from the Arctic. Better understanding of the moisture sources of precipitation in the polar regions will help us constrain models and predictions of glacial and sea ice coverage of the polar regions under current and future climate conditions. In this paper, depth profiles of stable isotopes, salinity, and ice texture of sea ice samples were described to serve as illustrations of the structures of the refrozen melt ponds in the Arctic. An isotope tracer mixing model was developed to determine the seasonality of meteoric water input for sea ice water balance. Key Points: The presence of meteoric origin isotopic signals as relatively thin layers indicates melt pond water stability during refreezing A dual‐isotope (oxygen isotope and deuterium excess) mixing model was utilized to determine the seasonality of meteoric water input The meteoric water signals of refrozen melt ponds were found near the surface or bottom, which may be due to different surface topography